Development of an innovative mechatronic binder machine - Sousa, João Pedro Ribeiro de (2022)
This paper describes the development of a mechatronic punch and bind office machine. Integrating smart technologies in the existing traditional business machines will ease the evolution of these systems, enabling productivity and efficiency. The development of an experimental platform that enables further advances in servitization is required. To increase the binding rate of the office document, as well as to reduce the likelihood of errors, efforts have been made to develop a measuring system that allows the document to be properly measured and specifies the appropriate binding spine at the same time. As a complement, developments have been conducted in a system that enables the verification of the inserted spine. In addition, a system for automated document binding along with an integrated platform that allows the communication between all systems is presented. In both its hardware design and its underlying sensors, the new system has several advantages, providing significant performance improvements and upgradability over existing systems. This alternative comprises a system that enables a variety of sheets of paper, plastic or other materials to be punched.